Acute correction, open wedge osteotomy and proximal tibial plate for severe recurrence and late onset blount's' Disease - preliminary results - Abdul Razak, Ardilla Hanim; Sharifudin, Mohd Ariff; Awang, Mohd Shukrimi (2014)
Background: To review early result of corrective osteotomy using a surgical technique of ‘Oblique Biplanar Opening wedge Medial Proximal Tibial Osteotomy’ for correction of genu varum in severe recurrence and neglected Blount’s’ disease using the Proximal Tibial Plate. Methodology: Three knees in 3 patients (2 male and 1 female) with recurrence or neglected Blount’s’ disease were recruited. Patients’ age varied from 9 to 11 years. Two knees out of 3 patients were cases of recurrence genu varum following corrective osteotomy done earlier at the age of 4 years old, and the other one knee was a new case. Pre and post-operative medial proximal tibial angle (MPTA) and mechanical axis deviation ( MAD) were measured both lower limbs. Operative technique: An oblique osteotomy was made over the posterior two thirds of proximal tibia metaphysis (just above the pes anserinus insertion) from inferomedial to superolateral aspect breaking the far cortex. The anterior third was cut at 45 degrees downwards to avoid the patella tendon and epiphysis. The distal fragment was rotated externally, translated laterally and angulated into valgus to correct the deformity. The resultant anatomical correction was secured with locking plate and fibula strut graft. Results: At the mean follow up of 8 months, we achieved a mean correction of 20 degrees (pre-operative mean deviation of MPTA from normal of 30 degrees to 4 degrees post operatively. There was no neuro-vascular complication, delayed union or loss of correction post operatively. All patients were able to fully weight-bear at four months time and were satisfied with the correction obtained. Conclusion: The surgical method of acute opening wedge osteotomy using a proximal tibial plate is a safe and stable fixation, which not required external support such as cast or brace in obese patient with recurrence and late onset Blount’s disease. This procedure has the advantage of allowing correction of large angular magnitude acutely, while avoiding the complications associated with gradual correction using external fixators.